Assessment of autonomic nervous system function in a patient suffering from multiple sclerosis - a case study - Karolina Kubiak; Martyna Lamtych; Klaudia Kwiatkowska; Nataliia Badiuk (Kazimierz Wielki University, 2018)
Background: Multiple sclerosis (MS) is a chronic demyelinating disease of the nervous system. In its course, there are many motor and non-motor disorders, including the autonomic system disorders. They are characterized by an increase or decrease in the activity of the autonomic nervous system. The course of the disease is most often multi-phase, there are periods of remission and exacerbation. The aim of the study is to assess cardiovascular parameters and heart rate variability in response to orthostatic stimuli in a patient with multiple sclerosis. Material and Method: A 48-year-old woman suffering from multiple sclerosis for 10 years (a form of secondary progressive disease) participated in the study. A study was carried out for cardiovascular response and heart rate variability in response to orthostatic stimuli. For this purpose, the Task Force Monitor system was used, which is a non-invasive method that allows the assessment of hemodynamic parameters such as heart rate, systolic blood pressure, diastolic blood pressure, and peripheral vascular resistance. Spectral heart rate variability (HRV) analysis was also used to assess the function of the autonomic nervous system. The evaluated parameters were: low-frequency component (LF), high-frequency (HF) and sympathetic-parasympathetic balance factor (LF / HF). Results: In the rest position, an autonomic balance shift was observed towards sympathetic domination. After performing the tilt test, the patient had an after pionization drop in blood pressure (orthostatic hypotension) as well as vascular resistance. Conclusions: The analysis of the case study shows that in multiple sclerosis there may be disorders of the autonomic nervous system manifested by abnormal regulation of arterial pressure in a vertical position.